Counting missing babies in Tanzania: Neonatal mortality data quality from Tanzania’s District Health Information System across 28 Regional and 7 Tertiary hospitals (2015–2024) - Josephine Shabani; Nahya Salim; Lucas Malla; James H. Cross; Rebecca E. Penzias; Audêncio Victor; Christine Bohne; Ahmad Mohamed Makuwani; Habib Ismail; Felix Bundala; Claud Kumalija; Morris Ondieki; et al. (PLoS ONE, 2026)
Introduction The Sustainable Development Goal 3.2 targets reducing the neonatal mortality rate (NMR) to <12 per 1,000 live births by 2030; however, 65 countries, including Tanzania, remain off track. The 2022/23 Tanzania Demographic and Health Survey (TDHS) reported an NMR of 24 per 1,000 live births, equivalent to 48,000 neonatal deaths annually. Methods Neonatal deaths were extracted from the District Health Information System (DHIS2) for 28 Regional Referral Hospitals (RRHs) and seven tertiary hospitals from 2015 to 2024. Data quality was assessed by: (1) completeness, as the proportion of months each hospital reported neonatal deaths; (2) internal consistency, comparing mean NMR for 2021–2023 with 2024 following WHO guidance; and (3) external plausibility, comparing DHIS2 with DHS and UN estimates. For seven hospitals implementing NEST360 program, NMRs from DHIS2 were compared with the Neonatal Inpatient Dataset (NID) for 2021 and 2024. Results Between 2015 and 2024, DHIS2 recorded an average of >8,500 neonatal deaths annually versus 48,000 expected. RRHs accounted for 30–40% of reported deaths, and tertiary hospitals for 4–11%. Overall monthly reporting completeness was 58.3%, higher in RRHs (median 61.7%, IQR 8.3–95.0%) than in tertiary hospitals (median 50%, IQR 0.8–73.3%), with only 8 RRHs (28.5%) and no tertiary hospital achieving >75% reporting. Only 28.6% of hospitals had internal consistency (NMR within ±33% of the mean) for 2021–2023. The DHIS2 NMR for 2024 was 5.9 per 1,000 (adjusted for ~20% home births), compared to 24 per 1,000 in DHS 2022/23. Compared with NEST360 NID, one tertiary hospital reported lower DHIS2 NMRs, and three RRHs reported higher (ratio >1). Conclusion Neonatal mortality reporting in Tanzania’s DHIS2 remains substantially under-captured, with notable variations across facilities. Although RRHs perform better than tertiary hospitals, overall data quality remains low. Improving reporting in underperforming facilities and leveraging high-performing RRHs can strengthen national neonatal mortality monitoring.